Oro-facial malignancy in north of Iraq: a retrospective study of biopsied cases - Sura Ali Ahmed Fuoad; Dena Nadhim Mohammad; Marwa Abdul-Salam Hamied; Balkees Taha Garib (BMC, 2021)
Abstract Background Identifying the prevalence of orofacial malignancies is essential to provide health-care programs and services for a specific population. This study aimed to specify the prevalence, clinical and histopathological features of oral malignancies in Sulaimani for over 12 years. Methods All archived reports for orofacial specimens from 2008 to 2019 were collected from three major centers in Sulaimani governorate. The demographic data, date, type of surgery, lesion's site, and diagnosis were recorded. The ICD-10 coding was specified for each case. A Chi-square test was used to assess differences between genders. A one-way ANOVA test was applied to analyze the differences in mean age distributions among different sites of oral malignancies and oral squamous cell carcinoma histopathological grades. P < 0.05 was considered significant. Results Orofacial malignant lesions account for 14.53% of the total sample. Patients' mean age was (55.46 ± 18.48) years, and they were predominantly males (M: F ratio = 1.15:1). The tongue was the frequently affected site (14.8%). A Chi-square test showed no significant difference between genders concerning age (P = 0.118), years of registration (P = 0.28), and site (P = 0.29). The C06 (represents; cheek mucosa C06.0, the vestibule of mouth C06.1, retromolar area C06.2, and other unspecified parts of mouth C06.8) was the most frequent topographical ICD-code (18.1%). Carcinoma was a frequent malignancy (63.2%). OSCC was the most common lesion (56.4%). It commonly affects males, and the tongue was the frequent site (24.1%) followed by lip (17.8%). Conclusions There is a slight increase in the registered oral malignancies in Sulaimani city over 12 years; they were predominated in males, in 61-70 years old patients, and being oral squamous cell carcinoma types.